Latour, Bruno, (2021). After Lockdown: A Metamorphosis - Konrad, Tatiana (Journal of Ecohumanism, 2022)
Latour, Bruno, (2021). After Lockdown: A Metamorphosis, trans. Julie Rose, Polity Press, 2021, 180 pages. Â£14.99 ISBN: 9781509550029